Associação entre os ácidos graxos plasmáticos poli-insaturados ômega-3 (N3-PUFA) e a força de preensão manual isométrica de acordo com os níveis de hemoglobina glicada em indivíduos acima de 50 anos: resultados da National Health And Nutrition Survey (NHANES) 2011-2012. - Batista, Raíssa Aparecida Borges (2022)
Background: Muscle strength is an important component of sarcopenia and a predictor of mortality with aging. While the hyperglycemia seem induce lower muscle strength, the omega-3 seem to have a beneficial influence on muscle strength and may promote a protective effect. However, the association between plasma omega-3 polyunsaturated fatty acids (n3-PUFA), and muscle strength in the older adults population with altered and unaltered glycohemoglobin levels has not yet been investigated. Objective: To evaluated whether n3-PUFA plasma levels are associated with isometric handgrip strength in individuals over 50 years old with altered and unaltered levels of glycohemoglobin included in the NHANES 2011-2012. Methods: This cross-sectional study included a total of 952 older adults individuals (50-85 years) from the NHANES 2011-2012 who had complete data on plasma omega-3 levels, glycohemoglobin levels, and handgrip strength. Linear regression analysis was performed with stratification of altered (≥ 5.7%) and unaltered (< 5.7%) glycohemoglobin levels without and with adjustments. Results: A high proportion of altered glycohemoglobin (49.7%) were observed. Although the n3-PUFA plasma levels were not different by groups, individuals with altered glycohemoglobin presented lower mean handgrip strength (63.1±21.7kgf). There was no association between plasma levels of n3-PUFA and handgrip strength. Conclusion: The n3-PUFA plasma levels of were not associated with handgrip strength in individuals over 50 years old with altered or unaltered glycohemoglobin levels. However, experimental studies can be carried out for a controlled evaluation of the omega-3 potential in this population.